OPTIMIZATION OF ALKALINE Α-AMYLASE PRODUCTION BY THERMOPHILIC BACILLUS SUBTILIS - Al-Johani, Nuha Bakeet; Al-seeni, Madeha N.; Ahmed, Youssri Mohamed (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Starch‐degrading amylase enzyme is important in biotechnological applications as food, fermentation,textile, paper and pharmaceutical purposes. The aim of current study to isolate alkaline thermostable α-amylase bacteria andthen study the composition of medium and culture conditions to optimize cells growth and a-amylase production.Materials and Methods: Thermophilic amylase producing bacterium was isolated from local hot water-springs in Gazancity Saudi Arabia.Results: Phylogenetic analysis of 16 S rRNA sequence for the strain revealed that the strain have the same sequence ofBacillus subtilis. Maximum amylase production was observed, when B. subtilis cultured in medium containing starch atconcentration 0.5%, and 10 g/L peptones as nitrogen source at pH 8.5 in when it was incubated for 48 h at 45°C.Conclusion: An amylase-producing bacterium were isolated from hot-spring water and was identified as B. subtilis.Amylase produced from B.subtilis had optimum temperature 45°C and pH 8.5 in shaking media.